Some physical characteristics of double-networked natural rubber - Kaang Shinyoung; Gong Donghwa; Nah Changwoon (Journal of Applied Polymer Science, 1997)
A double-networked natural rubber (DNNR) was prepared by a twp-step crosslinking method, in which the crosslinking was achieved while the natural rubber was in stretched condition. The swelling behavior, tensile properties, crepe, recovery, and permanent set were considerably improved as the residual extension was increased. They were, however, rather inferior to those of a single-networked natural rubebr and showed a minimum at a lower residual extension of about 1.55. The degree of crosslinking and elongation at break were not greatly affected by the resudal extension.
Keywords: Crepe and recovery; Double networks; Natural rubber; Swelling; Tensile property